Effect of Dietary Flaxseed Intake on Circulating Sex Hormone Levels among Postmenopausal Women: A Randomized Controlled Intervention Trial. (3rd April 2019) - Chang, Vicky C.; Cotterchio, Michelle; Boucher, Beatrice A.; Jenkins, David J. A.; Mirea, Lucia; McCann, Susan E.; Thompson, Lilian U.
Abstract: Lignan intake, and its richest food source, flaxseed, have been associated with reduced breast cancer risk. Endogenous sex hormones, such as estrogens, play a role in breast cancer development, and lignans may alter these sex hormone levels. To assess the effect of flaxseed on circulating sex hormones, a randomized controlled trial was conducted among 99 postmenopausal women in Toronto, Canada. The intervention arm consumed 2 tablespoons (15 g) of ground flaxseed daily for 7 weeks; the control arm maintained usual diet. Baseline and week 7 concentrations of 14 serum sex hormones were measured using liquid chromatography–tandem mass spectrometry (LC-MS/MS) and immunoassay, and serum enterolignans (lignan biomarker) using LC-MS/MS. Intervention effects on sex hormone levels were assessed using analysis of covariance. Serum enterolignans increased among the flaxseed arm (+516%). Women consuming flaxseed (vs. controls) had increased serum 2-hydroxyestrone [treatment effect ratio (TER) = 1.54; 95% CI: 1.18–2.00] and 2:16α-hydroxyestrone ratio (TER =1.54; 95% CI: 1.15–2.06); effects on other hormones were not statistically significant. Within the flaxseed arm, change in enterolignan level was positively correlated with changes in 2-hydroxyestrone and 2:16α-hydroxyestrone ratio, and negatively with prolactin. Findings suggest flaxseed affects certain circulating sex hormone levels with possible implications for future breast cancer prevention research.